Parent-child relationship, socio-economic status, peer-pressure and self-esteem as predictors of juvenile delinquency behaviour in Ibadan, Nigeria (2020)
Anti-social behaviours are often associated with juvenile delinquency. This societal menace motivated the investigation of parent-child relationship, parental socio-economic status, peer pressure and self-esteem as determinants of juvenile delinquency among adolescents in Ibadan Metropolis. The study adopted correlational survey design. A randomly selected sample of two hundred and twenty (220) secondary school adolescents was used Two research questions were raised and answered while four hypotheses were formulated and tested at 0.5 level of significance. Five reliable measuring instruments adapted and validated to form a structured questionnaire were used for data analysis. Pearson product moment correlation and multiple regression analysis were used to analyse the data. The study showed there was a significant relationship between the Independent and Dependent Variables. Multiple regression analysis revealed that: there was a significant joint contribution of Independent to Dependent Variables, the most potent factor was peer-pressure (β=.189, t=2.859, p<.05), followed by self-esteem (β= -.244, t= -3.362, p<.05), parent-child-relationship (β= -.420, t= -5.835, p< .05) and parental socio-economic status (= -.017, t= -.795). This implies that self-esteem and parent-child relationship will reduce juvenile delinquency by 24.4% and 42% respectively while peer-pressure will increase juvenile delinquency by 18.9%. It was therefore recommended that school administrators should constitute a disciplinary committee to checkmate social menace and discipline offenders in the school; Federal Government could build correctional homes to rehabilitate delinquent adolescents for reformation to be useful to themselves and the society at large.